On Study of Vertex Labeling of Graph Operations - Rajan, M. A.; Kembhavimath, N. M.; Lokesha, V. (Journal of Scientific Research, 2011)
Vertices of the graphs are labeled from the set of natural numbers from 1 to the order of the given graph. Vertex adjacency label set (AVLS) is the set of ordered pair of vertices and its corresponding label of the graph. A notion of vertex adjacency label number (VALN) is introduced in this paper. For each VLS, VLN of graph is the sum of labels of all the adjacent pairs of the vertices of the graph. is the maximum number among all the VALNs of the different labeling of the graph and the corresponding VALS is defined as maximal vertex adjacency label set . In this paper for different graph operations are discussed. Keywords: Subdivision; Graph labeling; Direct sum; Direct product. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i26222 J. Sci. Res. 3 (2), 291-301 (2011)